Isokinetic knee muscular strength is associated with hematologic variables in female modern dancers - (:unkn) unknown (UNIV ALICANTE, 2018)
It is important to expose the risk factor in injury in the context of the health and the careers of dancers. Female are at greater risk of developing anemia than men, yet scarce data exist on anemia associated outcomes in female dancers. The aim of the present study was to investigate the relationships between bilateral isokinetic knee extensor and flexor muscles strength, and biochemical hematologic parameters in female modern dancers. Concentric isokinetic peak torque [(PT)-N.m], peak torque % body weight [(PT% BW)-N.m.kg(-1)], average peak torque [(AVGPT)-N.m] and total work [(TW)-J)] of the knee extensor and flexor muscles were measured at a velocity of 60 degrees, 180 degrees and 300 degrees s(-1). To determine hematological parameters [red blood cell count (RBC), hematocrit (Hct), and Hb] were determined. The dancers of LHG and HHG had significant differences (p <= 0.05) for hematological parameters. HHG dancers' strength production in extensors muscles of PT, TW and AVGPT in non-dominant left leg (p <= 0.05) were significantly higher than LHG dancers. There were significant (p <= 0.05) negative correlations between TW (300 degrees s(-1)) of left leg extensor muscles and RBC, Hct and Hb variables. Isokinetic knee muscular strength is associated with hematologic variables in female modern dancers. The current study provides evidence that the low-level hematologic parameters has decreased performance on torque production of extensors knee muscles in non-dominant leg during isokinetic muscle strength endurance in female modern dancers.
Keywords: HEMOGLOBIN; MUSCLE STRENGTH; ATHLETIC PERFORMANCE; DANCING; IRON STATUS; SPORTS; INJURIES; PERFORMANCE